The Development of Local Culture Based Teaching Materials with Constructivism Approach to Improve the Thinking Ability and Mathematics Disposition of Student - Sri Rahma Yani Harahap; Izwita Dewi; Mulyono Mulyono (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research is a development research conducted at SMP N 2 Panyabungan which aims to find out how; 1) the level of validity, effectiveness and practicality of teaching materials developed in improving students' mathematical reasoning abilities and dispositions; 2} Increasing students' mathematical reasoning skills and dispositions in the application of local culture-based teaching materials with a constructivism approach. This research produces teaching materials based on local culture with a constructivism approach that is carried out according to the Dick & Carey development model procedure. The results of this study are the local culture-based teaching materials developed are; 1) valid, both this validity and construct, 2) effective, seen from the completeness of learning and student activities; 3) practical, seen from the validator's assessment and students' positive responses to the teaching materials developed; 4) to increase students' mathematical reasoning abilities in the application of teaching materials based on local culture, namely 0.19; 5) the improvement of students' mathematical disposition abilities in the development of teaching materials, namely 0.43.